2020
DOI: 10.1021/acs.chemmater.0c02051
|View full text |Cite
|
Sign up to set email alerts
|

Site-Specific Protein Conjugation onto Fluorescent Single-Walled Carbon Nanotubes

Abstract: Semiconducting single-walled carbon nanotubes (SWCNTs) are among the few photostable optical emitters that are ideal for sensing, imaging, drug delivery, and monitoring of protein activity. These applications often require strategies for immobilizing proteins onto the nanotube while preserving the optical properties of the SWCNTs. Site-specific and oriented immobilization strategies, in particular, offer advantages for improving sensor and optical signaling responses. In this study, we demonstrate site-specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 61 publications
0
17
0
Order By: Relevance
“…In recent years, different studies have demonstrated the importance of controlling the position and orientation of the biomolecule relative to the SWCNT: biomolecules, and particularly proteins, are not uniform structures, as nanoparticles are, and therefore the point at which they are tethered is important to consider [7,11,21]. This has been shown to have significant effects in the protein/SWCNT interactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, different studies have demonstrated the importance of controlling the position and orientation of the biomolecule relative to the SWCNT: biomolecules, and particularly proteins, are not uniform structures, as nanoparticles are, and therefore the point at which they are tethered is important to consider [7,11,21]. This has been shown to have significant effects in the protein/SWCNT interactions.…”
Section: Introductionmentioning
confidence: 99%
“…This has been shown to have significant effects in the protein/SWCNT interactions. Zubkovs et al and Thomas et al [11,21] have shown how the site-specific attachment of a fluorescent protein affects the optical behavior of both protein and SWCNTs; this was demonstrated by investigating the change in a fluorescent protein function and, in the case of Zubkovs et al, of (7,6) SWCNTs within a mixture of nanotubes. There are other examples of changes in the fluorescent behavior of SWCNTs due to biofunctionalization, but these investigations are typically carried out with unsorted SWCNTs; hence, the interaction can only be considered an average response to each species in the mixture.…”
Section: Introductionmentioning
confidence: 99%
“…ssDNA-EYFP bioconjugation was performed as described previously [29]. The purified EYFP was reduced using 10 mM Tris(2-carboxyethyl)phosphine hydrochloride (TCEP, ABCR) in EDTA-PBS buffer for 1 h while shaking at 500 rpm in an Eppendorf thermomixer at 5 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Despite being highly hydrophobic nanostructures, SWCNTs can be easily suspended in aqueous solution using noncovalent functionalization by polymers, DNA, RNA, dendrons, proteins, peptides, or specific recognition elements like antibodies or aptamers [ [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] ]. Only functionalized, suspended SWCNTs reveal a fluorescence signal.…”
Section: Introductionmentioning
confidence: 99%